Development of a real-time dose monitor with Cr-doped Gd3Ga5O12 infrared scintillator. (November 2017) - Kurosawa, Shunsuke; Yamaji, Akihiro; Kochurikhin, Vladimir V.; Ivanov, Mikhail; Pejchal, Jan; Murakami, Rikito; Shoji, Yasuhiro; Ohashi, Yuji; Yokota, Yuui; Kamada, Kei; Yoshikawa, Akira
Abstract: The development of a real-time dose monitor system is one of the important issues in medical engineering to reduce medical accidents such as overdose or incorrect positioning of the treated human tissue during radiation therapy. One of the challenging solutions is to use an infrared scintillator, which is sufficiently bright so that the light can be detected outside the human tissue. In this study, a novel infrared scintillator, Cr-doped Gd3 Ga5 O12, was tested with pork meat as a phantom of human tissue to prove its feasibility for the dose monitor. The scintillation photons of Cr:Gd3 Ga5 O12 were observed through even 50-mm thick pork meat. The emission peak originated from d-d emission of Cr 3+ . The emission intensity of Cr:Gd3 Ga5 O12 was approximately 3.5 times larger than that of the conventional infrared scintillator Cr:α-Al2 O3 . Moreover, we succeeded in performing the infrared imaging for Cr:Gd3 Ga5 O12 irradiated with alpha-rays using a complementary metal oxide semiconductor camera. Highlights: Cr-doped Gd3 Ga5 O12 was used as infrared scintillator. Radiation imaging was obtained with infrared photons from the scintillator. It is Feasibility study for the dose monitoring in real time for radiation therapy. Imaging test was operated with pork meat as a phantom of human tissue.